Connectivity and closeness among international financial institutions: a network theory perspective. Issue 3 (2018) - Warin, Thierry; Sanger, William
This article focuses on connectivity and closeness between financial institutions. Financial institutions are a subset of multinational corporations and play an important role in our modern economies. By studying connectivity and closeness, this article proposes a network theory approach to the notion of systemic risk. Using network theory, we propose to look at potential networks between financial institutions through their boards of directors. Measures of centrality (degree, closeness, betweenness, eigenvalue) and force-directed networks are provided for each country. We built a large sample (43, 399 individuals; 2, 209 institutions) across 52 countries using Bureau van Dijk's database. We find corporate interlocks showing - to some degree - the level of concentration within the financial system. The main contribution of this article is to show some evidence of small-world properties of the international financial system; the ramifications of this question could be critical, notably in terms of systemic risk.